Cost-effective isolation of Viburnum opulus-derived nanovesicles and evaluation of their cytotoxic, anticancer, and antioxidant properties on human glioblastoma cell line U87MG - Giritlioglu, Nazli Irmak; Poyraz, Fatma Sayan; Mansuroglu, Banu; Erisen, Semiha (HUMANA PRESS INC, 2025)
Glioblastoma is the most common and highly invasive glial tumor, significantly reducing patient survival. Current therapeutic approaches have limited success rates. Plant-derived nanovesicles are a rapidly developing area, recognized for their exceptional biofunctional properties, and are emerging as a promising approach in cancer treatment. The present study focuses on the isolation of nanovesicles from Viburnum opulus fruits using a cost-effective method that includes a polymer-based exosome precipitation buffer and size exclusion chromatography, followed by their characterization. Morphological analysis via Field Emission Scanning Electron Microscopy and Transmission Electron Microscopy revealed nanovesicles ranging from oval to elliptical shapes, with average diameters of 54.23 nm and 41.21 nm, respectively. Dynamic light scattering analysis determined the average size of 45.36 nm indicating the presence of nanovesicles, and the zeta potential was - 2.87 mV. Biochemical characterization showed total protein and phenolic concentrations of 1534 +/- 97.78 mu g/ml and 4.270 +/- 0.66 mg gallic acid equivalents/L, respectively, with total antioxidant status values of 3.83 +/- 0.37 mmol Trolox equivalents/L. Based on IC50 values, these nanovesicles were 7.5 times more toxic to U87MG human glioblastoma cells compared to healthy human dermal fibroblasts. Analyses including clonogenic cell survival, wound healing, apoptosis, total antioxidant status, and total oxidant status were continued on only U87MG cells, as human dermal fibroblasts showed a low response to nanovesicle treatment. Qualitative and quantitative assessments demonstrated that Viburnum opulus-derived nanovesicles effectively inhibited cancer cell proliferation and migration. Due to their non-toxic, anticancer, and antioxidant properties, these nanovesicles hold significant potential in glioblastoma management.
Keywords: Exosome; Glioblastoma; Nanovesicle; Plant-derived nanovesicle; Viburnum opulus; BLOOD-BRAIN-BARRIER; ASSAY; NANOPARTICLES; Oncology